(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
The purpose of this research is to determine the influence of teacher’s work motivation on teacher’s performance, the influence of principal’s leadership on teacher’s performance, and the influence of teacher’s work motivation and principal’s leadership together on the performance of high school teachers in East Baturaja District, Ogan Komering Ulu Regency. This research was carried out at 4 high schools in East Baturaja District, Ogan Komering Ulu Regency. This type of research is quantitative research. The population in this study was 110 with a sample of 86 respondents. The data collection techniques in this research used three methods, namely questionnaires, documentation, and observation. The results obtained in this research are that there is a significant influence between teacher’s work motivation on the performance of high school teachers in East Baturaja District, Ogan Komering Ulu Regency. There is a significant influence between principal’s leadership on the performance of high school teachers in East Baturaja District, Ogan Komering Ulu Regency and there is a significant joint influence between teacher’s work motivation and principal’s leadership on the performance of high school teachers in East Baturaja District, Ogan Komering Ulu Regency.